Visualization of PMMA blood analogue fluid flowing through a hyperbolic microchannel - Calejo, Joana A.C. (2018)
Axial migration of individual red blood cells (RBCs) is a well known effect that happens in microchannels with dimensions below 300 μm. This effect is known as the Fåhræus-Lindqvist effect gives place to a cell free layer (CFL) of plasma located around the walls of the microchannel [1]. Several flow studies regarding the CFL measurement exist in in vitro [1-3] environments. However, the manipulation of in vitro blood is often difficult due to the ethical, economical and safety issues involved. As a result, the development of blood analogue solutions is needed to improve our understanding regarding the blood flow behaviour in microchannels and microvessels. Although several studies using one-phase Newtonian and non-Newtonian blood analogues can be found in the literature [4, 5], there are few works related with the use of particulate solutions in which the particles mimic the RBCs behaviour. The present work proposes a particulate-viscoelastic solution made of xanthan gum and dextran with rigid polymethylmethacrylate (PMMA) spherical particles able to mimic the effect of CFL formation that frequently happens in in vitro blood flow systems. Flow visualizations through hyperbolic contraction microchannels were used to observe the CFL originated by the proposed blood analogue fluid. Additionally, this CFL was compared with the plasma layer formed by an in vitro blood sample.